This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
z 1 8 = 1 has roots z = 1 , e 9 π i , e 9 2 π i , e 9 3 π i , . . . . . . e 9 1 6 π i , e 9 1 7 π i , then z 1 8 − 1 = ( z − 1 ) ( z − e 9 π i ) ( z − e 9 2 π i ) ( z − e 9 3 π i ) , . . . . . . ( z − e 9 1 6 π i ) ( z − e 9 1 7 π i ) Now dividing L.H.S. and R.H.S. by (z-1), and taking limits at z = 1, 1 8 = ( 1 − e 9 π i ) ( 1 − e 9 2 π i ) ( 1 − e 9 3 π i ) , . . . . . . ( 1 − e 9 1 6 π i ) ( 1 − e 9 1 7 π i ) . Multiplying by its conjugate gives, 1 8 2 = 2 1 7 ( 1 − c o s 9 π ) ( 1 − c o s 9 2 π ) ( 1 − c o s 9 3 π ) , . . . . . . ( 1 − c o s 9 1 6 π ) ( 1 − c o s 9 1 7 π ) . Now putting 1 − c o s 2 θ = 2 s i n 2 θ everywhere thus halving angles 1 8 2 = 2 1 7 ( 2 s i n 2 1 8 π ) ( 2 s i n 2 1 8 2 π ) ( 2 s i n 2 1 8 3 π ) , . . . . . . ( 2 s i n 2 1 8 1 6 π ) ( 2 s i n 2 1 8 1 7 π ) . Taking square-root 1 8 = 2 1 7 ( s i n 1 8 π ) ( s i n 1 8 2 π ) ( s i n 1 8 3 π ) , . . . . . . ( s i n 1 8 1 6 π ) ( s i n 1 8 1 7 π ) . Now use the fact that first and last factors are equal as s i n θ = s i n ( π − θ ) and as s i n 1 8 9 π = 1 , taking square-root once again we get the desired answer as ( 2 1 6 9 ) = 2 5 6 3 .